Identification of bacteria and fungi sampled from the conjunctival surface of normal horses in South‐East Queensland, Australia. (2nd July 2018) - Hampson, Edith C. G. M.; Gibson, Justine S.; Barot, Mayank; Shapter, Frances M.; Greer, Ristan M.
Abstract: Objective: To identify bacteria and fungi found on the conjunctival surface of normal horse eyes; to investigate potential risk factors for these microflora; and to determine their susceptibility to common topical ophthalmic antimicrobials. Animals studied: A total of 95 client‐owned horses were studied. Procedures: Horses within sub‐tropical Australia (South‐East Queensland) were sampled once between April 2012 and March 2013. A conjunctival swab was taken from each eye and cultured for aerobic bacteria and fungi. Organisms were identified by colony morphology and phenotype. Antimicrobial disk diffusion susceptibility testing for commonly used antimicrobials was performed. Results: Positive bacterial cultures were returned from 187/190 (98.4%) eyes from 94/95 (98.9%) horses. The most common species included Staphylococcus spp. (25.2% of total bacterial isolates), Bacillus cereus (17.4%), Bacillus spp. (14.1%), and Corynebacterium spp. (8.9%). Most bacterial isolates were susceptible to neomycin and fluoroquinolones. Positive fungal cultures were returned from 111/190 (58.4%) eyes from 73 (76.8%) horses. The most common species identified included: Penicillium spp. (16.7% of fungal isolates), Aspergillus spp. (15.4%), and Scopulariopsis spp. (10.3%). Most (≥90%) molds were susceptible to ketoconazole, voriconazole, itraconazole, and miconazole. Yeasts were most susceptible to ketoconazole. There was no significant effect of breed, age, sex, purpose, or housing of the horse or climatic conditions on bacterial or fungal culture status. Conclusions: Bacteria and fungi were commonly isolated from the eyes of healthy horses. The antibiotic and antifungal susceptibilities identified can be used as a guide for empirical therapy after cytology in the treatment of corneal ulceration in horses.